Stable discretization methods with external approximation schemes. (1995) - Verma, Ram U.
Abstract : We investigate the external approximation-solvability of nonlinear equations- an upgrade of the external approximation scheme of Schumann and Zeidler [3] in the context of the difference method for quasilinear elliptic differential equations.